Maternal obesity and the risk of neural tube defects in offspring: A meta-analysis. Issue 2 (March 2017) - Huang, Hai-Yan; Chen, Hong-Lin; Feng, Li-Ping
Summary: Objectives: The aim of this was to access maternal obesity and the risk of neural tube defects (NTDs) in offspring, and establishes a nonlinear dose–response relationship between maternal body mass index (BMI) and risk of NTDs in offspring. Methods: PubMed and Web of Science were systematically searched. We compared NTDs risk difference in maternal obesity group vs. normal weight group + overweight group, and maternal obesity group vs. normal weight group. We also examined the dose–response relationship between maternal body mass index and the risk of NTDs in offspring. Results: A total of 22 studies with 1, 758, 832 patients included in the meta-analysis. The results showed obesity maternal obesity is an important risk factor for NTDs in offspring. When maternal obesity group compared with normal weight group + overweight group, the summary OR of NTDs was 1.632 (95% CI 1.473–1.808; Z = 9.37, P < 0.00001); when maternal obesity group compared with normal weight group, the summary OR was 1.682 (95% CI 1.510–1.873; Z = 9.44, P < 0.00001). No publication biases were found. Dose–response meta-analysis showed statistically significant association between maternal BMI and risk of NTDs in offspring (model χ 2 = 41.49, <0.00001). In linear model, the OR of NTDs in offspring was 1.040 (95% CI 1.027–1.051) for every 1 kg/m 2 BMI increase in mother. In spline model, the OR of NTDs in offspring risk increased rapidly along with maternal BMI, especially when BMI >30 kg/m 2 . Sensitivity analyses by only included the studies reported adjusted OR showed the result was robust. Conclusion: Our meta-analysis indicated that maternal obesity is an important risk factor for neural tube defects in offspring.